Value of general surgical risk models for predicting postoperative morbidity and mortality in pancreatic resections for pancreatobiliary carcinomas. (19th March 2014) - Haga, Yoshio; Wada, Yasuo; Saitoh, Toshihiro; Takeuchi, Hitoshi; Ikejiri, Koji; Ikenaga, Masakazu
Abstract Background The present study evaluated the utility of general surgical risk models to predict postoperative morbidity and mortality in the specialty field of pancreatic resections for pancreatobiliary carcinomas. Methods We investigated Estimation of Physiologic Ability and Surgical Stress (E‐PASS), its modified version (mE‐PASS), and Portsmouth Physiologic and Operative Severity Score for the enUmeration of Mortality and morbidity (P‐POSSUM) in 231 patients undergoing pancreatoduodenectomy or distal pancreatectomy (Group A). We also analyzed E‐PASS and mE‐PASS in another cohort of the same procedures (Group B, n = 313). Results Areas under the receiver operating characteristic curve (AUC) for detecting in‐hospital mortality in Group A were moderate at 0.75 for E‐PASS, 0.69 for mE‐PASS, and 0.69 for P‐POSSUM. The predicted mortality rates of the models significantly correlated with severity of postoperative complications (ρ = 0.17, P = 0.011 for E‐PASS; ρ = 0.15, and P = 0.027 for P‐POSSUM). The AUCs were also moderate in Group B at 0.68 for E‐PASS and 0.69 for mE‐PASS. The predicted mortality rates significantly correlated with severity of postoperative complications (ρ = 0.18, P = 0.0018 for E‐PASS; ρ = 0.17, and P = 0.0022 for mE‐PASS). Conclusions The present study suggests that the predictive powers of general risk models may be moderate in pancreatic resections. A novel model would be desirable for these procedures.